Five Years after the Great Hanshin-Awaji Earthquake A Study for Revealing University Students Experiences on it - NAKAZONO, Shinji; MINAMI, Satoshi (The Japanese Journal of Safety Education, 2001)
The purpose of this study was to clarify university students experiences on the Great Hanshin-Awaji Earthquake. On January 17,1999, five years after the earthquake, a questionnaire survey was administered to ask 164 university students to describe their experiences on it. Most of them were junior high school students at the time of the earthquake. So, there were not many subjects who did direct activities in the struck area. But, their experiences on the great earthquake were a precious opportunity by which they considered not only the disaster and importance of the anti-disaster measures, but also human life/death and kindness, etc. At the time of five years after the earthquake, they were forgetting seriousness of the disaster, but the lesson of it must not be faded away. Whether we had the experiences of suffering the earthquake disaster or not, it is necessary that we should develop safety education on disaster prevention, disaster prevention measures, and rehabilitation and therapy of earthquake victims.